AN ANALYSIS OF COMMUNICATION STRATEGIES USED BY TEACHER IN ENGLISH TEACHING AND LEARNING AT SMA SARASWATI SINGARAJA - ., Kadek Windayanti; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Universitas Pendidikan Ganesha, 2017)
This qualitative research aimed at (1) finding out the types of communication strategies used by teacher during English teaching and learning proses; (2) analysing the English teacher?s reasons in applying the communication strategies; (3) analysing the students` perception toward the implementation of communication strategies used by the teacher. The subjects of this study were English teacher and XI grade students of SMA Saraswati Singaraja. The data were collected through direct observation and interview. Besides, observation sheet, video recorder, voice recorder, interview guide and field note were also used to collect the data. The result of this research showed that there were 14 types of communication strategies which were applied by the teacher namely: literal translation, code switching, non-linguistics signal, message abandonment, circumlocution, self-repair, approximation, use of fillers or time-gaining strategy, repetition, comprehension check, asking for repetition, guessing, interpretive summary, and response. From those strategies, code switching was the strategy that was most frequently used by the teacher during the process of teaching and learning. Meanwhile, message abandonment and interpretive summary had the lowest frequency of occurrence during the teaching and learning process. The teacher`s reasons for applying those communication strategies were to overcome the communication barriers that occur between the teacher and the students, to help the students understand and memorize the material easier. Moreover, the other teacher`s reasons for applying communication strategies were to make the learning process more interesting and make the students more focus to the lesson. The result of the interview also showed that the students had good perception toward the implementation of communication strategies used by the teacher in the classroom. keyword : communication strategies, English teacher, Dornyei and Scott`s theory, qualitative study.